Transnational management : text, cases, and readings in cross-border management - Bartlett, Christopher A. , 1943-; Beamish, Paul W. , 1953- (McGraw-Hill Irwin, 2014)
Focuses on management challenges associated with developing strategies and managing operations of companies whose activities stretch across national boundaries. This book provides a conceptual framework showing the interplay between multinational corporation, countries in which it does business, and competitive environment in which it operates.